2005
DOI: 10.1037/0893-3200.19.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Sibling relationships in early/middle childhood: links with individual adjustment.

Abstract: The overarching goal of the study was to identify links between sibling relationship quality in early/middle childhood with children's adjustment, having accounted for the effects of parent-child relationship quality. The sample consisted of 101 working and middle-class 2-parent English families with 2 children ages 4-8 years. Parents provided reports of sibling relationship quality, the parent-child relationship, and the children's prosocial and problematic behaviors. The children also provided reports of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
151
4
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(178 citation statements)
references
References 29 publications
4
151
4
12
Order By: Relevance
“…Furthermore, sibling relationships are independently associated with later adolescent adjustment and well-being, even after controlling for parental and peer influences [17][18][19] .…”
Section: Siblingsmentioning
confidence: 96%
“…Furthermore, sibling relationships are independently associated with later adolescent adjustment and well-being, even after controlling for parental and peer influences [17][18][19] .…”
Section: Siblingsmentioning
confidence: 96%
“…Similarly, despite the well-established relevance of sibling relationships for both individual and family experience and development (Buist, Deković, & Prinzie, 2013;Feinberg, Solmeyer, & McHale, 2012;Pike, Coldwell, & Dunn, 2005), few studies explore sibling relationships in the context of DV (Piotrowski, Tailor, & Cormier, 2014a;Piotrowski, 2011), particularly using a qualitative approach (Waddell, Pepler, & Moore, 2001). This is particularly surprising if we consider that most families experiencing DV have more than one child and that sibling relations can play a crucial role as either risk factors and protective factors in each other's unique developmental trajectories, wellbeing and adjustment (Gass, Jenkins, & Dunn, 2007;Pike et al, 2005).…”
Section: Copingmentioning
confidence: 99%
“…Siblings' varying perceptions and reactions to stressful family events are often reduced to individual differences between them (e.g. birth order, age and gender, length of exposure), and psychological accounts rarely investigate and grasp their personal and highly contextual lived experience of sibling relationships (Pike et al, 2005;Piotrowski, Tailor, & Cormier, 2014b). Sibling relationships are often 5 only explored in DV literature with regards to sibling violence (Khan & Rogers, 2015;Pinel-Jacquemin, Cheron, Favart, Dayan, & Scelles, 2012;Sims et al, 2008), which is often understood as emotional and behavioural 'spillover' from the parental to the sibling subsystem (Pike et al, 2005) or the older sibling to the younger one (Piotrowski et al, 2014b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies in which the participants were siblings of different ages (hereafter, singleton siblings), emotional support and social learning provided important benefits for children's social adjustment. Previous studies have found that emotional support from a sibling is associated with positive peer relationships and promotes the development of children's social adjustment (Lamarche et al, 2006;Pike et al, 2005;Rinaldi & Howe, 1998). In addition, Hughes and Leekam (2004) showed that social learning from a sibling promotes the development of social skills.…”
mentioning
confidence: 99%